2017
DOI: 10.1038/nature22992
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and functional regulatory mutations in breast cancer

Abstract: Genomic analysis of tumours has led to the identification of hundreds of cancer genes on the basis of the presence of mutations in protein-coding regions. By contrast, much less is known about cancer-causing mutations in non-coding regions. Here we perform deep sequencing in 360 primary breast cancers and develop computational methods to identify significantly mutated promoters. Clear signals are found in the promoters of three genes. FOXA1, a known driver of hormone-receptor positive breast cancer, harbours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
300
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 72 publications
7
300
1
2
Order By: Relevance
“…RMRP acts as a sponge for miR-206 an oncogene in lung cancer (Meng, et al 2016). Deep sequencing of 360 primary breast tumors identified mutations in the promoters of lncRNAs RMRP and NEAT1 that increased their expression and noted increased expression of these lncRNAs in breast tumors (Rheinbay, et al 2017). However, RMRP's role in BCa remains to be fully elucidates and no publications were found with respect to RMRP in prostate, endometrial, ovarian, or thyroid cancer.…”
Section: Mitochondrial-encoded Lncrnas and Lncrna Imported Into Mitocmentioning
confidence: 99%
“…RMRP acts as a sponge for miR-206 an oncogene in lung cancer (Meng, et al 2016). Deep sequencing of 360 primary breast tumors identified mutations in the promoters of lncRNAs RMRP and NEAT1 that increased their expression and noted increased expression of these lncRNAs in breast tumors (Rheinbay, et al 2017). However, RMRP's role in BCa remains to be fully elucidates and no publications were found with respect to RMRP in prostate, endometrial, ovarian, or thyroid cancer.…”
Section: Mitochondrial-encoded Lncrnas and Lncrna Imported Into Mitocmentioning
confidence: 99%
“…Epigenetic adaptations may provide initial resistance and allow tumor cells to survive until they acquire secondary mutations that further drive progression (16,45,46). Furthermore, mutations in noncoding regions, such as enhancers and promoters, influence gene expression and can be new drivers for cancer progression and evolution (47)(48)(49).…”
Section: Alk-rearranged Patient Samplesmentioning
confidence: 99%
“…There are examples where the non-coding regulatory mutations are involved in tumorigenesis like the TERT promoter in melanoma (Horn et al, 2013;Huang et al, 2013) and in other cancers (Vinagre et al, 2013), and recurrent non-coding mutations in chronic lymphocytic leukaemia (CLL) (Puente et al, 2015) and breast cancer (Rheinbay et al, 2017). However, these studies have each identified a small number of .…”
Section: Introductionmentioning
confidence: 99%